147 Patients demographics and predictors of violence: a 5-year experience of a level 1 trauma centre. (19th September 2017) - El-Menyar, Ayman; Samson, David; Tilley, Elizabeth; Gashi, Saranda; Prabhakaran, Kartik; Latifi, Rifat
Abstract : Background: Although Violence is a preventable phenomenon, it remains a challenging public health concern worldwide. We aimed to assess the characteristics and predictors of violence among patients who were admitted to a level 1 trauma centre in a single institution. Methods: We conducted a retrospective analysis of all patients who were admitted to the trauma section with a history of assault as the cause of injury at Westchester Medical Centre, New York, between 2012 and 2016. Multivariable logistic regression analysis was performed to assess the predictors of violence. Results: A total of 9856 trauma patients were admitted across the study period, of whom 746 (7.6%) had a history of assault prior to the index admission. Patients who had history of assault were 13 years younger, and more likely to be males (89% vs 63%), Black ( 36% vs 9%), Hispanic (22% vs 13%) and covered by low-income primary payer (53% vs 17%) in comparison to non-assault trauma patients (p<0.001). Also patients with assault were more likely to have penetrating injuries (33% vs 5%), arrived from home (18% vs 11%), referred from another facility (62.5% vs 48%) and presented with injury to the face (53% vs 15%), p=0.001. Overall mortality (4.5% vs 0.8%) and hospital complications were more evident among non-assault trauma patients. Multivariate logistic regression analysis showed that covariate-adjusted predictors of violence were being Black [Odd Ratio (OR) 5.51], male (OR 3.45), having low-income primary payer (OR 2.80), Asian (OR 2.22), drug user (OR 1.82), alcohol intoxicated (OR 1.77), and smoker (OR 1.73). Conclusions: admission to hospital due to violence is a problem among young age subjects with certain demographic, social and ethnic characteristics. There is a need for scaling up our commitment to promoting the prevention of violence.